Eco-innovation and retailers in milk, beef and bread chains: enriching environmental supply chain management with insights from innovation studies. (16th November 2015) - Mylan, J.; Geels, F.W.; Gee, S.; McMeekin, A.; Foster, C.
Abstract: This paper investigates why, how and to what degree supermarkets stimulate upstream eco-innovation in UK milk, beef and bread chains. To answer this question, we aim to enrich the environmental supply chain management literature with insights from innovation studies. The resulting conceptual framework distinguishes three elements: a) motivations for supermarkets to address eco-innovation (internal considerations and external pressures), b) characteristics of supply chains that hinder or enable eco-innovation attempts (e.g. breadth, length, degree of trust), c) mechanisms to stimulate eco-innovation. Regarding this third element, which is our main contribution, we distinguish: 1) economic mechanisms (supermarkets paying farmers more for eco-innovation or imposing eco-performance standards), 2) information exchange and interactive learning in networks ('innovation systems'), and 3) socio-cognitive coordination through the creation of shared meaning and visions (e.g. roadmaps). We demonstrate the usefulness of this framework with a comparative qualitative analysis of three UK sectors with different degrees of retailer-led eco-innovation: milk, beef and bread. The paper ends with three broader reflections and suggestions for further research.